Summer fades, deer change: Photoperiodic control of cellular seasonal acclimatization of skeletal muscle - Kristina Gasch; Alba Hykollari; Manuela Habe; Patricia Haubensak; Johanna Painer-Gigler; Steve Smith; Gabrielle Stalder; Walter Arnold (iScience, 2024)
Summary: We found major seasonal changes of polyunsaturated fatty acids (PUFAs) in muscular phospholipids (PL) in a large non-hibernating mammal, the red deer (Cervus elaphus). Dietary supply of essential linoleic acid (LA) and α-linolenic acid (ALA) had no, or only weak influence, respectively. We further found correlations of PL PUFA concentrations with the activity of key metabolic enzymes, independent of higher winter expression. Activity of the sarcoplasmic reticulum (SR) Ca++-ATPase increased with SR PL concentrations of n-6 PUFA, and of cytochrome c oxidase and citrate synthase, indicators of ATP-production, with concentrations of eicosapentaenoic acid in mitochondrial PL. All detected cyclic molecular changes were controlled by photoperiod and are likely of general relevance for mammals living in seasonal environments, including humans. During winter, these changes at the molecular level presumably compensate for Arrhenius effects in the colder peripheral body parts and thus enable a thrifty life at lower body temperature.